The Role Of The United Nations High Commissioner For Refugees In Handling Refugees In Ethiopia 2020-2022: Peran United Nations High Commissioner For Refugees Dalam Menangani Pengungsi Di Ethiopia Tahun 2020-2022 - Salsabila, Amanda (TRANSBORDERS: International Relations Journal, 2025)
Abstract: This study aims to describe the role of the United Nations High Commissioner for Refugees (UNHCR) in managing refugees in Ethiopia from 2020 to 2022. The armed conflict between the Tigray People’s Liberation Front (TPLF) and the Ethiopian government on November 4, 2020, caused a large wave of refugees. UNHCR, as an international organization, played a key role in providing humanitarian aid and protection to the refugees. This research uses a descriptive study with a qualitative approach supported by the Theory of International Organization Roles. Data was collected through primary interviews and secondary sources such as documents, books, journals, and previous research. The findings reveal that UNHCR carried out three key roles as an international organization: 1) Instrumental Role: UNHCR supported Ethiopia’s national interests by providing shelter, food, healthcare, education, and WASH (Water, Sanitation, and Hygiene) services. 2) Facilitative Role: UNHCR served as a platform, such as the Refugee Coordination Group (RCG), to discuss the Comprehensive Refugee Response Framework (CRRF) and support development programs. 3) Actor Role: UNHCR took responsibility for creating policies and ensuring protection for refugees and asylum seekers. It actively participated in programs for protection, community resilience, aid distribution, capacity building, and refugee solutions. Although UNHCR has provided significant aid and development plans, there is a need for more trained personnel, such as teachers and healthcare workers. Additionally, increased funding is required to improve infrastructure and expand partnerships. Keywords: International Organization, UNHCR, Refugees, Ethiopia, Humanitarian Aid